INTERPRETATION CONTROVERSY TOWARDS ONLINE LEARNING IN ENGLISH INSTRUCTION DURING COVID-19 IN INDONESIA - Siswoyo, Siswoyo; Fatma Yuniarti (Universitas Negeri Surabaya, 2023)
Corona virus disease has various impacts to the people’s activities. Many countries were not allowed their citizens to go from their places. Their works were done from their homes using online facilities. The schools were closed and the teaching and learning process were conducted through online. These were all done to stop the corona virus disease spreading. Online learning instead of offline learning faced controversy among the people especially parents. The objectives of the current research were to investigate (1) the forms of controversy on online learning, (2) factors that affect the controversy, and (3) implications towards the implementation of teaching and learning process. The current research used qualitative approach. There were 24 participants who joined in the current research. The data were collected through questionnaires. The results of the current research were (1) the respondents agree and disagree with the use of online learning, (2) they said that online learning made them easy and some of them said that online learning was problem, (3) the implication of the online learning was that the parents felt frustrated to face online learning and some of them had no problem. Online learning had advantages and disadvantages. Further research should conduct the research using more participants to make the research more comprehensive.